Application of material flow cost accounting (MFCA) in microalgae manufacturing company in Malaysia / Mageswaran Murugiya - Mageswaran, Murugiya (2018)
Malaysian government showed special interest in manufacturing greener product and raising awareness regarding the environmental pollution due to industrialization. Frameworks from standards such as Life Cycle Assessment (LCA), Environmental Management Accounting (EMA) and a series of ISO14000 to reduce the environmental impact due to manufacturing. Material Flow Cost Accounting (MFCA), ISO 14051 is one of the principal tools used under EMA that focuses on establishing monetary unit on the waste generated in the processes involved in the manufacturing company. MFCA allows the company to track wastes and reducing it in each key process in the manufacturing company but there are few challenges that faced by Malaysian SMEs in implementing MFCA. The selected company for the study is a microalgae manufacturing company, ABC Sdn.Bhd. in Malaysia. The total material, energy, system and waste management costs were drawn out by constructing the material flow and the costs associated with it. Based on the specific objects of the study, all the costs relevant to MFCA is collected from the company and represented in the material flow matrix and calculated to identify the costs associated with the non-product output from the manufacturing process. Percentage of material input into products and material losses were taken into consideration in allocating system and energy costs in the single manufacturing line. For allocation of energy there were aspects taken into consideration; the running time of the machine and the efficiency of the machine in the production line. Result shows that 89.49% of the total cost allocated for the material while other costs about 10.50%. The costs allocated for the product accounted for 82.13% while cost of material losses in this process in general takes another 17.87%. As a result, the company realized that there is a room for improvement for reduction of material losses in the company. It was also found that the highest material lost was in the energy lost which is about 40.52% compared to assumed by the company which is more or less about 10%. It was clearly seen that the company is losing more than 17% of their investment in the production that rather could be used for the improvement in efficiency of the machines and energy. The company also recommended to apply MFCA in all line of production to evaluate the total costs associated in the overall material losses thus it can be reduced.